Recurrent cystitis and bacterial vaginosis: how to avoid polypharmacy - Ekaterina V. Kulchavenya; Aleksandr A. Breusoff (IP Berlin A.V., 2020)
Background. The structure of lower urinary tract infections has clear sex-based differences. The vaginal microbiota is a key factor in the pathogenesis of lower urinary tract infections: aerobic vaginitis predisposes to infection and increases the incidence of cystitis by 2.9 times. Aim. To determine the effectiveness of Nifuratel as monotherapy in patients with chronic cystitis and concomitant bacterial vaginosis (BV). Materials and methods. Study design: an open-label, non-comparative, pilot, single-center, prospective study, which included 23 patients with recurrent cystitis and BV. All women received monotherapy with Nifuratel (Macmiror manufactured by Doppel Farmaceutici S.r.l., Italy) in tablets of 200 mg 3 times a day for 7 days. Control visits were performed in 7.90 and 180 days. Results. BV was diagnosed in all patients; 19 (82.6%) women also had vaginal candidiasis. At the end of therapy, 17 (73.9%) patients showed an excellent outcome, 4 (17.4%) a significant improvement, 2 (8.7%) no effect. After the end of three-month therapy, 18 (81.8%) out of 22 patients who left in the study had no complaints of urinary disorders or vaginal discharge. Their urinalyses were normal. Molecular genetic analysis of the vaginal biocenosis showed moderate dysbiosis; Candida spp. was revealed only in 3 (13.6%) cases. 18 patients came for the 4th visit. Within six months after the end of monotherapy with Nifuratel, the patients had no complaints. They all achieved the recovery of vaginal normocenosis with a sufficient amount of Lactobacillus spp. Conclusion. Monotherapy in patients with recurrent cystitis and BV is highly effective for both diseases: 73.9% of women achieved stable normalization of urine and vaginal microbiota analyzes, removal of bacteriuria. The bi-directional action of Nifuratel allows to avoid polypharmacy in this category of patients.